Políticas, cultura y prácticas inclusivas en el personal auxiliar del Campus Sur de la Universidad Nacional de Chimborazo. - Guizado González, Lady Johanna (2025)
The Universidad Nacional de Chimborazo (UNACH), at its La Dolorosa campus, promotes an inclusive culture, norms, and practices that guarantee an equitable and accessible environment for all auxiliary personnel, regardless of their personal, social, cultural, or disability characteristics. This contributes to their well-being and integral development. The objective of the research was to strengthen UNACH's inclusive culture and improve its attention to diversity. Using a qualitative approach, data were collected through interviews and focus groups to understand the fundamentals of an inclusive culture and develop a methodological strategy that allows its effective implementation. In addition, it is necessary to emphasize that the Ecuadorian State complies with the provisions of the law and is committed to guaranteeing the fundamental rights of inclusion by adopting all administrative, legal, economic, and social measures that promote true inclusion. Ecuador has promoted legislative reforms to promote equality for all. At the constitutional level, the Ecuadorian State has the duty to guarantee equal access to fundamental rights such as education, health, work, and social security and to strengthen national unity in diversity. Therefore, the Universidad Nacional de Chimborazo implemented clear strategies and regulations, such as regulations, policy manuals, and specific protocols for the care of people in vulnerable situations. Inclusion within the university community is key to personal and professional development, allowing auxiliary staff to train and actively participate in their work environment. At the Universidad Nacional de Chimborazo (UNACH), the implementation of inclusion standards not only improves the welfare of employees but also strengthens institutional quality by fostering an environment of respect, empathy, and appreciation of diversity. At UNACH, inclusion has a comprehensive approach since it prioritizes excellence in service, empathy in interactions, and effective communication. This includes strategies to improve user relationships. At the cultural level, it promotes an inclusive environment that values diversity regarding culture, ethnicity, language, and gender.